Cardiopulmonary Dysfunction and Adiponectin in Adolescents With Type 2 Diabetes. Issue 3 (18th March 2016) - Bjornstad, Petter; Truong, Uyen; Dorosz, Jennifer L.; Cree‐Green, Melanie; Baumgartner, Amy; Coe, Gregory; Pyle, Laura; Regensteiner, Judith G.; Reusch, Jane E. B.; Nadeau, Kristen J.
Abstract : Background: Myocardial mechanics are altered in adults with obesity and type 2 diabetes (T2D); insulin resistance and adipokines have been implicated as important risk factors for cardiovascular disease, but these relationships are poorly described in adolescents. We hypothesized that obese adolescents and adolescents with T2D would have abnormal cardiac function compared to lean adolescents. In addition, we hypothesized that insulin sensitivity (IS), adiposity, and adipokines would be associated with altered cardiac strain and cardiopulmonary fitness in adolescents with T2D. Methods and Results: Adolescents (15±2 years) with T2D (n=37), obesity without diabetes (n=41), and lean controls (n=31) of similar age and pubertal stage underwent echocardiography with speckle tracking, assessment of IS by hyperinsulinemic–euglycemic clamp, body composition by dual‐energy x‐ray absorptiometry, peak oxygen consumption (VO2 peak) by cycle ergometry, adiponectin, and leptin. Compared to lean and to obese controls, adolescents with T2D had significantly lower cardiac circumferential strain (CS) (−18.9±4.6 [T2D] versus −21.5±3.5 [obese] versus −22.0±4.2% [lean], P =0.04) and VO2 peak (37.6±7.5 [T2D] versus 43.4±8.2 [obese] versus 47.6±8.6 mL/lean kg/min [lean], P <0.0001). In T2D youth, VO2 peak was associated with CS, and the association remained significant after adjusting for age, sex, and IS (β±SE: −0.73±0.26, P =0.02). Among adolescents with T2D, CS was also associated with adiponectin, longitudinal strain with leptin, and VO2 peak with adiponectin and IS. Conclusions: Adolescents with T2D had abnormal CS and reduced VO2 peak compared to obese and lean controls, which may represent the earliest evidence of cardiac functional impairment in T2D. Low adiponectin, rather than conventional risk factors and IS, correlated with CS, while both adiponectin and IS related to cardiopulmonary fitness.